Traditional Chinese Medicine nursing by regulating Liver for patients with hyperthyroidism (甲状腺功能亢进症的中医从肝护理) - ZHANG Xixia (章细霞); AN Zhentao (安振涛); WANG Bei (王蓓) (中西医结合护理)
Hyperthyroidism, as known as goiter in Traditional Chinese Medicine (TCM), is a common endocrine disease which mainly affecting the thyroid gland. According to TCM theorysyndrome of liver-qi stagnation may be the main factor leading to the occurrence of hyperthyroidism. This paper summarized the TCM nursing by regulating Liver in perspectives of daily living habits, dietary guidance, emotional care and complications, in order to provide reference for the clinical nursing practice for patients with hyperthyroidism. (甲状腺功能亢进症是临床常见的内分泌疾病, 属于中医“瘿病” “瘿气”的范畴, 病位在甲状腺, 与肝脏功能密切相关, 其病因与肝郁气结有关。本文从生活起居、饮食护理、情志护理、并发症护理等方面探讨从肝施护的措施, 以期为临床护理该类疾病提供可靠思路。)